MANAJEMEN UNIT USAHA PESANTREN - Maidah Sufiani; Inayah Ratih (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2021)
The purpose of this study is to find and describe the independence of pesantren through pesantren business units in the form of tofu factories and analyze the development of pesantren independence capital, analyze factors supporting the formation of pesantren independence and analyze obstacles to the formation of pesantren independence. The research method used isqualitative metode using primary data sources through interviews about data and information related to research. The economic development of pesantren through the tofu factory business unit established in 2013 that gets a loan of funds from pesantren, with profits obtained for the initial return on capital. Marketing through offline and online where santri also plays a role in the economic development of pesantren which is also currently acting as a transaction. Its financial statements are conducted weekly and monthly collected to benhara Koppontren. The management of pesantrren business units in the form of factories know must be developed by improving its marketing model which not only has a target market in its own pesantren but with other pesantren and the general public.